KEBIJAKAN PEMERINTAH INDONESIA MENDUKUNG PROGRAM SUSTAINABLE DEVELOPMENT (STUDI KASUS MANAJEMEN LIMBAH PT CHEVRON PACIFIC INDONESIA) - Mohammed Ghazi Anwar; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the policy of Indonesia government support sustainable development program in case waste management in Chevron Pacific Indonesia Company. Environment issue are one of the most important issues in international relations. One of the program to thinking green are sustainable development programs to maintanance of environment.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the role of international organization for migration in antisipated human trafficking in Indonesia. The theories applied in this research are realism perspective with decision making theory by Graham T Allison.The conclusion of this research the policy of Indonesia government support sustainable development program in case waste management in Chevron Pacific Indonesia Company are with rativication of international convention in environment issue, implementation of international standart operation in environment issue, Indonesia Government create a PROPER programs and create some regulations as a rule of waste management.Key words: policy, environment, waste and management.